Pyoluteorin-deficient Pseudomonas protegens improves cooperation with Bacillus velezensis, biofilm formation, co-colonizing, and reshapes rhizosphere microbiome - Qian Zhao; Ruoyi Wang; Yan Song; Juan Lu; Bingjie Zhou; Fang Song; Lijuan Zhang; Qianqian Huang; Jing Gong; Jingjing Lei; Suomeng Dong; Qin Gu; et al. (npj Biofilms and Microbiomes)
Abstract Plant-beneficial Pseudomonas and Bacillus have been extensively studied and applied in biocontrol of plant diseases. However, there is less known about their interaction within two-strain synthetic communities (SynCom). Our study revealed that Pseudomonas protegens Pf-5 inhibits the growth of several Bacillus species, including Bacillus velezensis. We established a two-strain combination of Pf-5 and DMW1 to elucidate the interaction. In this combination, pyoluteorin conferred the competitive advantage of Pf-5. Noteworthy, pyoluteorin-deficient Pf-5 cooperated with DMW1 in biofilm formation, production of metabolites, root colonization, tomato bacterial wilt disease control, as well as in cooperation with beneficial bacteria in tomato rhizosphere, such as Bacillus spp. RNA-seq analysis and RT-qPCR also proved the pyoluteorin-deficient Pf-5 mutant improved cell motility and metabolite production. This study suggests that the cooperative effect of Bacillus–Pseudomonas consortia depends on the balance of pyoluteorin. Our finding needs to be considered in developing efficient SynCom in sustainable agriculture.